Conveying Supervisory Practices and Their Influence in Teaching-Learning Effectiveness - Jovelyn W. Narabe; Rufino T. Tudlasan, Jr. (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
This research examined the relationship between the supervisory practices of school heads and the teaching–learning performance of the teachers in Subangdaku Elementary School in School Year 2024 -2025. Specifically, it sought to determine the respondents’ demographic profiles, the extent of school heads’ supervisory practices, the level of teachers’ teaching–learning performance, and the significance of their relationship. The study employed a descriptive correlational research design with school heads and teachers as respondents. Data were gathered through a structured survey questionnaire and analyzed using the weighted mean and t-test. Findings revealed that most respondents were females aged 31 – 40 years, married, and master’s degree holders with 11 – 15 years of service. Supervisory practices were highly implemented across five domains, namely, Classroom Observation, Post-Observation Feedback and Coaching, Professional Development and Training Support, Monitoring and Evaluation, and Lesson Planning and Preparation, with Classroom Observation obtaining the highest mean. Teachers likewise demonstrated a high level of teaching–learning performance, particularly in Learner Engagement, while Lesson Planning and Preparation received the lowest mean. Results showed a significant relationship between supervisory practices and teaching–learning performance, leading to the rejection of the null hypothesis. Based on these findings, a Supervisory Practices in Teaching–Learning Enhancement Plan was developed to strengthen developmental supervision, improve instructional planning, and sustain professional growth among teachers. It was recommended that the proposed plan be adopted to guide school heads in promoting effective supervision, institutionalizing continuous professional development, and enhancing instructional quality toward improved learning outcomes in basic education.